Cyber War : Ancaman Baru Keamanan Nasional dan Internasional (Cyber War: New National and International Security Threat) - Yanuar, Adams Pratama (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2021)
Currently, international issues have shifted from traditional issues to nontraditional issues (contemporary). In the past, in the era of World War 1 and 2, physical warfare became a major issue in the international world. However, now that the world has experienced a digital era, the main issue in the international world has shifted from physical warfare to digital warfare or commonly known as Cyber War. Cyber War is a digital war which can be in the form of data robbery or important sector information sectors such as intelligence, national code, foreign policy strategy, national defense, military, etc. So that later the data will be used for the benefit of data thieves. This research will focus on Cyber War Threats on an international scale and the impact that will result from the existence of Cyber War. By using qualitative and quantitative methods, the data presented in this study can be justified. So that this research is considered important enough to add insight and knowledge related to international conditions and threats in the future.